2019
DOI: 10.1002/hed.25773
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on post‐thyroidectomy morbidity

Abstract: Background The impact of obesity on total thyroidectomy (TT) morbidity (recurrent laryngeal nerve palsy and hypocalcaemia) remains largely unknown. Methods In a prospective study (NCT01551914), patients were divided into five groups according to their body mass index (BMI): underweight, normal weight, overweight, obese, and severely obese. Preoperative and postoperative serum calcium was measured. Recurrent laryngeal nerve (RLN) function was evaluated before discharge, and if abnormal, at 6 months. Results In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
(48 reference statements)
4
12
0
Order By: Relevance
“…Most of the studies conducted so far on the correlation between elevated BMI and postoperative morbidity in the field of thyroid surgery confirm our findings [ 4 , 10 13 , 15 ]. Only three studies documented an increased occurrence of complications [ 5 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…Most of the studies conducted so far on the correlation between elevated BMI and postoperative morbidity in the field of thyroid surgery confirm our findings [ 4 , 10 13 , 15 ]. Only three studies documented an increased occurrence of complications [ 5 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…Controversy remains whether obesity increases intra-and postoperative morbidity. A recent prospective analysis did not reveal higher complication rates, despite a longer duration of the procedure (30). This finding conflicts with previous studies advocating that bariatric surgery should be performed first (31,32).…”
Section: Discussionmentioning
confidence: 63%
“…Past/current smoker 11,913 (20) 673 (15) 3231 (17) 3870 (21) 3221 (23) 918 ( 25 19,747 (33) 1388 (32) 6010 (31) 6219 (34) 4820 (35) 1310 ( 35)…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we consider that both underweight and overweight patients with thyroid cancer can undergo surgery as safely as patients with normal BMI, and clinicians must pay attention to general complications in obese patients. Previous studies have demonstrated discordant results regarding the association between BMI and short-term outcomes following thyroid cancer surgery (18,19,20,21), presumably because these studies failed to adjust for certain patients' background characteristics (e.g. cancer stage, intraoperative device use and some comorbidities).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation